MicroRNAs reshape the immunity of insects in response to bacterial infection - Abbas, Muhammad Nadeem; Kausar, Saima; Asma, Bibi; Ran, Wenhao; Li, Jingui; Lin, Zini; Li, Tiejun; Cui, Hongjuan (Frontiers in Immunology, 2023)
Bacteria are widely distributed across the globe, and those with impaired immune systems, as well as other susceptible individuals, are at increased risk of contracting an infection from them. In addition, they have been linked to high mortality rates in economically important insects, resulting in huge economic losses. MicroRNAs (miRNAs) are a class of small non-coding RNAs that regulates gene expression post-transcriptionally. The length of miRNAs ranges from 19 to 22 nucleotides. MiRNAs, in addition to their ability to exhibit dynamic expression patterns, have diverse range of targets, allowing them to govern a variety of physiological processes, including the innate immune response in insects. A growing body of evidence indicates that miRNAs play a crucial biological role in bacterial infection by influencing immune responses and other resistance mechanisms. This review focuses on some of the most recent and exciting discoveries made in recent years, such as the correlation between aberrant expression of miRNAs with bacterial infection progression. Furthermore, it describes how they have a profound impact on the immune responses of the host by targeting the Toll, IMD, and JNK signaling pathways. It also emphasizes the biological role of miRNAs in the regulation of immune responses in insects. Finally, it also discusses current knowledge gaps regarding the function of miRNAs in immunity, as well as areas that require further research in the future.